Audit culture as disruptive praxis of uni¬versity practices (Praxis Educativa, 2012)
The purpose of this paper is to present an analysis of the transformations of academic practices based on an examination of an emergent notion in the field of Higher Education: audit culture. We posit some structuring facets of the traditional organisation of university culture and then we concentrate on the central aspects of what is known as “audit culture”, implemented globally in the last decades. The re-configuration of higher education policies and the means generated from the disruptive rationality of audit culture show a change to a conception of university organisation which is congruent with the pragmatic values of liberal capitalism. At the end of this paper we present some of the transformations carried out in university practices due to the implementation of new management issues.
Keywords: organisational culture; university; audit culture; organisational change